A modeling method for dumbbell‐shaped DGS and its parameter extraction. Issue 12 (December 2014) - Woo, Duk‐Jae; Lee, Taek‐Kyung; Nam, Sangwook
ABSTRACT This article presents an equivalent circuit model for a dumbbell‐shaped defected ground structure (DGS) in a microstrip line. The effects of equivalent circuit elements of a dumbbell‐shaped DGS and their magnetic coupling to the host transmission line are modeled as a simple lumped‐element circuit. By adding a virtual capacitor on the narrow etched gap, the values of inductance and capacitance of the dumbbell‐shaped DGS in the ground plane were extracted. Also, other main circuit parameters of the proposed circuit model were extracted using EM simulation result. This article provides one approach for understanding the operating principle of the DGS structures. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2910–2913, 2014